Ability of procalcitonin to discriminate infection from non-infective inflammation using two pleural disease settings. - Fiona J McCann; Stephen J Chapman; Wai Cho Yu; Nick A Maskell; Robert J O Davies; Y C Gary Lee (PLoS ONE)
Unlabelled Procalcitonin has been shown to be useful in separating infection from non-infective disorders. However, infection is often paralleled by tissue inflammation. Most studies supporting the use of procalcitonin were confounded by more significant inflammation in the infection group. Few studies have examined the usefulness of procalcitonin when adjusted for inflammation.Pleural inflammation underlies the development of most exudative effusions including pleural infection and malignancy. Pleurodesis, often used to treat effusions, involves provocation of intense aseptic pleural inflammation. We conducted a two-part proof-of-concept study to test the specificity of procalcitonin in differentiating infection using cohorts of patients with pleural effusions of infective and non-infective etiologies, as well as subjects undergoing pleurodesis. Methods We measured the blood procalcitonin level (i) in 248 patients with pleural infection or with non-infective pleural inflammation, matched for severity of systemic inflammation by C-reactive protein (CRP), age and gender; and (ii) in patients before and 24-48 hours after induction of non-infective pleural inflammation (from talc pleurodesis). Results 1) Procalcitonin was significantly higher in patients with pleural infection compared with controls with non-infective effusions (n = 32 each group) that were case-matched for systemic inflammation as measured by CRP [median (25-75%IQR): 0.58 (0.35-1.50) vs 0.34 (0.31-0.42) µg/L respectively, p = 0.003]. 2) Talc pleurodesis provoked intense systemic inflammation, and raised serum CRP by 360% over baseline. However procalcitonin remained relatively unaffected (21% rise). 3) Procalcitonin and CRP levels did not correlate. In 214 patients with pleural infection, procalcitonin levels did not predict the survival or need for surgical intervention. Conclusion Using a pleural model, this proof-of-principle study confirmed that procalcitonin is a biomarker specific for infection and is not affected by non-infective inflammation. Procalcitonin is superior to CRP in distinguishing infection from non-infective pleural diseases, even when controlled for the level of systemic inflammation.